(untitled) (Journal of Telenursing (JOTING), 2025)
This study aims to determine the Lean Six Sigma method in optimizing the lead time of pharmaceutical supplies at the University of Indonesia Hospital. The research method used is a qualitative design through an action research approach focusing on the internal process from submitting pharmaceutical supplies to supplies received by the pharmacy unit. The results of the study indicate that the description of the existing business process flow, then the existing waste can be identified, namely the length of the process that still needs much improvement. Making PO at ULP and receiving goods by logistics are the two processes that take the most time, so the drug supply procurement process takes 35 days. This causes the pharmacy to provide a buffer stock of 2 times the lead time waiting time, namely a buffer stock of 70 days, so drug services are not disrupted due to stock problems. This risks the hospital’s cash flow being hampered and the high default on each term of the hospital’s debt payment. Conclusion, The Lan Six Sigma method in optimizing the lead of the pharmaceutical supply team at the University of Indonesia Hospital has been carried out with the results of the search for the problem of the length of the lead time in pharmaceutical supplies found in several units related to the Supply Chain Management function, so it is necessary to ensure that each unit in it is consistent in holding their respective roles while making continuous improvements. Keywords: Lead Time, Lean Six Sigma Method, Pharmaceutical Supplies